Empirical Research on Education for Sustainable Development in Sufficiency-Based Schools - Suriyankietkaew, Suparak; Hallinger, Philip (European Journal of Sustainable Development, 2018)
Education for sustainable development becomes a mantra for scholars worldwide. Yet, empirical research in the field of education for sustainable development is underdeveloped, especially in an emerging Asian economy of Thailand. Thailand has progressed toward education for sustainable development with its sufficiency-based school movement to advance sustainability in education. It aims to develop and promote a whole-of-school approach to apply sufficiency thinking for sustainable development to all school activities from management and student activities to community partnerships. Sufficiency thinking is based on a framework of Sufficiency Economy Philosophy” (SEP)—an alternative approach to sustainable development, as advocated by UNDP and resonated with UN SDG Goals. To advance the limited knowledge in the field, this research paper empirically investigates what school management practices/factors, based on the SEP theoretical framework, can significantly predict enhanced education for sustainable development in schools. Survey data stem from 240 schools in Thailand. Based on results of factor analysis, a research model for educational sustainability was emerged and proposed. Findings from multiple regression analysis suggest that SEP principles, namely virtues, prudence, stakeholder focus and enabling culture, are significant predictors of enhanced education for sustainable development in Thailand, possibly applicable in other countries. Keywords: Education, sustainable development, sustainability, SDG, sufficiency economy, Asia, Thailand.